Design a microwave transmitter using magnetron and two layers waveguides - Ahmed Hameed Reja; Ahmed Abdulqader Hussein; Sabahaldin Abdulqader Hussain (Institute of Advanced Engineering and Science, 2023)
A magnetron is a power oscillator device used in several radar transmitters for generating the electromagnetic wave (EMW) with a constructive and fixed frequency. In this work, a radar transmitter has been carried out using magnetron operates at 2,458 MHz and two conducting layers waveguides to achieve minimum loss of the signal due to the increased temperature. The magnetron is connected with the high voltage capacitor (1.0 μF) in order to store the alternating current (AC) signal delivered from the high voltage transformer. A waveguide parts have been used as transmission lines in view of connecting the magnetron to the antenna. These parts include two metal layers, the upper layer (outer) is advanced audio coding (AAC) 1350 aluminum conductor and the lower (inner) is copper. The waveguide dimension should be suitable to flow frequency from 2.2 GHz to 3.3 GHz. To measure the operating frequency, a waveguide adapter and a coaxial cable which combined with n-female connector have been connected to magnetron. The wave is delivering to the frequency counter by Bayonet Neill–Concelman (BNC) to n-female connectors. The promising results of the proposed work have been achieved with a maximum power, efficient return loss, acceptable voltage standing wave ratio (VSWR) and low-cost manufacturing.